2004
DOI: 10.1159/000078819
|View full text |Cite
|
Sign up to set email alerts
|

Using Skin Models to Assess the Effects of a Protection Cream on Skin Barrier Function

Abstract: Background: There is a basic necessity to understand the mechanisms of the protective effects of emulsions. This would promote the development of protective cosmetics and therefore improve the prevention and treatment of occupational skin diseases. However, for such studies, no reliable skin model is available. Objective: An in vitro skin model test was developed to evaluate the protective mechanism of cosmetic ingredients. Methods: The efficacy of three products was assessed by an in vivo test (Repetitive Occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Therefore, in the present study we investigated the effects of a ceramide‐containing water‐in‐oil ointment on the physical skin barrier structure and function in a recently developed IL‐31 induced human 3D organotypic in vitro model of the disrupted skin barrier. Zur Mühlen and colleagues demonstrated that 3D skin models are a suitable tool to study barrier repair mechanisms and to gain insight into the protective and regenerative effects of cosmetic formulations . In order to obtain an AD‐like phenotype in our skin models, we treated these with IL‐31, as recently described .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study we investigated the effects of a ceramide‐containing water‐in‐oil ointment on the physical skin barrier structure and function in a recently developed IL‐31 induced human 3D organotypic in vitro model of the disrupted skin barrier. Zur Mühlen and colleagues demonstrated that 3D skin models are a suitable tool to study barrier repair mechanisms and to gain insight into the protective and regenerative effects of cosmetic formulations . In order to obtain an AD‐like phenotype in our skin models, we treated these with IL‐31, as recently described .…”
Section: Discussionmentioning
confidence: 99%
“…Zur Mühlen and colleagues demonstrated that 3D skin models are a suitable tool to study barrier repair mechanisms and to gain insight into the protective and regenerative effects of cosmetic formulations. [27] In order to obtain an AD-like phenotype in our skin models, we treated these with IL-31, as recently described. [9] We demonstrated that IL-31 weakens the formation of the lipid envelope and disturbs the differentiation process of keratinocytes by downregulating the expression of several structural proteins, including filaggrin.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared the barrier‐repair properties of 14S24 with the skin lipids using the Franz diffusion cell, full‐thickness porcine skin extracted by chloroform/methanol 2 : 1 and TH as a model permeant 14 . Recently, EpiDerm‐200‐HCF cultures exposed to SLS were studied as in vitro models to assess the effects of a protective cream on the skin barrier function 21 …”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, EpiDerm-200-HCF cultures exposed to SLS were studied as in vitro models to assess the effects of a protective cream on the skin barrier function. 21 In this study, we used ex vivo human skin combined with noninvasive methods and the penetration of a model compound into the dermis assessed by cutaneous microdialysis. The skin was disrupted by the solvent-induced lipid extraction, tape stripping and detergent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several in vivo and in vitro methods are in existence for the evaluation of BC. A commonly used in vivo method is the repetitive irritation test (3); in addition, diffusion cells and in vitro skin models have been used (4, 5). Furthermore, the penetration of various dyes after pretreatment with a BC was measured by skin reflectance measurements, chromameter or laser‐induced breakdown spectroscopy (6, 7, 8).…”
mentioning
confidence: 99%